Lesotho : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The Selected Issues paper provides an overview of trends, performance export growth, value added, and employment, account of the structure and evolution of Lesotho's textiles during the decade through 2002, and discusses future prospects and key issues. It analyzes the implications of the phasing-out of the African Growth and Opportunity Act and also reviews the HIV/AIDS situation in Lesotho. It discusses the current situation, the measures to enhance financial intermediation, and the Southern African Customs Union Arrangement and its effects on revenues. The paper also includes the summary of tax systems, July 2003, and the exchange trade system.